Simulasi Penggunaan Cisco Packet Treaser Untuk Protokol TCP dan UDP Dalam Topologi Jaringan Ring - Muhammad Abdullah Bin Matni; Raihan Ahmad Musyaffa; Umar Hamzah; Aini Nur Hayani; Didik Aribowo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to evaluate the performance of TCP and UDP protocols using Cisco Packet Tracer in a ring network topology. This simulation examines parameters such as latency, throughput, and packet loss for both protocols, and compares their effectiveness in different network scenarios. Simulation results show significant performance differences between TCP and UDP in a ring topology, with TCP showing higher reliability while UDP offers higher speed.